2016
DOI: 10.1093/intqhc/mzv123
|View full text |Cite
|
Sign up to set email alerts
|

Lean interventions in healthcare: do they actually work? A systematic literature review

Abstract: PurposeLean is a widely used quality improvement methodology initially developed and used in the automotive and manufacturing industries but recently expanded to the healthcare sector. This systematic literature review seeks to independently assess the effect of Lean or Lean interventions on worker and patient satisfaction, health and process outcomes, and financial costs.Data sourcesWe conducted a systematic literature review of Medline, PubMed, Cochrane Library, CINAHL, Web of Science, ABI/Inform, ERIC, EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
210
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 301 publications
(222 citation statements)
references
References 50 publications
3
210
0
5
Order By: Relevance
“…A recent systematic review of Lean initiatives in health found little evidence of quality improvement overall and singled out Saskatchewan's experience as costing far more to implement than was achieved in savings (Moraros, Lemstra and Nwankwo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of Lean initiatives in health found little evidence of quality improvement overall and singled out Saskatchewan's experience as costing far more to implement than was achieved in savings (Moraros, Lemstra and Nwankwo 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 22 studies using Lean processes, with quantitative data for health outcomes, process outcomes, or both health and process outcomes, did not show statistically significant results, although the data were too diverse for a meta-analysis. 17 Nonetheless, the authors found that there was no association between Lean methods and patient satisfaction or health outcomes. 17 Also, there might have been a negative association with costs and employee satisfaction.…”
Section: Implications and Significance For Practicementioning
confidence: 96%
“…17 Nonetheless, the authors found that there was no association between Lean methods and patient satisfaction or health outcomes. 17 Also, there might have been a negative association with costs and employee satisfaction. 17 Finally, the review showed inconsistent benefits in terms of patient flow and safety.…”
Section: Implications and Significance For Practicementioning
confidence: 96%
See 2 more Smart Citations